Relationship between running route and time in base running from the home plate to second base in collegiate baseball players - Imawaka, T.; Yanaka, T.; Tsunoda, N. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
"Base running" (BR) in baseball is a factor related to offense as well as hitting. A superior BR performance increases the on-base percentage and provides score run opportunity. Running routes are an important factor in BR. However, the relationship between a running route and time in BR is unclear. The aim of the present study was to clarify the relationship between running routes and time in BR from the home plate to second base. Fifteen male collegiate baseball players performed BR to second base from the home plate and 54.86 m of straight sprinting. The BR time, speed and route between the home plate and first base (HF) and between the first base and second base (FS) during base running were calculated using the three-dimensional panning DLT method, respectively. Indicators of the calculated running route in each section were 1) the vertical distance (VD) from the line between bases when the body position was projected on the ground, and 2) the position that recorded the maximum VD (VDp). The maximum speed in the HF section was 8.0±0.3 m/s, but in the FS section, the speed decreased to 6.9±0.4 m/s at minimum. On the other hand, there was no significant difference in the maximum speeds between HF and FS (7.9±0.4 m/s). The BR time to the second base showed a significant correlation with the maximum VD in HF (r = -0.631, p = 0.012), VDp in HF (r = 0.633, p = 0.011), the rate of deceleration from HF to FS (r = 0.612, p = 0.015) and the maximum speed in FS (r = -0.794, p <0.001). Besides, straight sprinting time was significantly correlated with maximum speed in HF and FS, but no correlations were found with running route variables. These results suggest that reducing the rate of deceleration and increasing the maximum speed in the FS section will shorten the BR time to the second base, which should be achieved by changing the route in the HF section.